An MBSE Eco‐System for Performing Trade‐off Analysis. Issue 4 (8th January 2019) - Hause, Matthew
ABSTRACT: A trade‐off study consists of "comparing the characteristics of each system element and of each candidate system architecture to determine the solution that best globally balances the assessment criteria. The various characteristics analyzed are gathered in cost analysis, technical risks analysis, and effectiveness analysis (NASA 2007)." Trade‐off analysis is the set of techniques by which the "best" solution is found for the customer weighing up cost, risk, effectiveness, and other parameters. The weighting or importance of these parameters depends on the system goals and priorities, which are derived from stakeholder needs, which are gathered from stakeholders. As always, good system solutions are derived from good systems engineering. Defining a decision framework that reflects competing goals, needs, priorities, parameters, and architectures in a clear and understandable way. Orthogonal Variability Modeling (OVM) provides the ability to model systems and software products, their variation points, mutual exclusions, and product dependencies resulting in product lines. OVM was developed by the University Duisburg‐Essen, PALUNO Institute [Paluno 2005], and is now ISO standard ISO 26550: 2013, Reference Model for System and Software Product Line Engineering and Management (ISO, 2013). Through this modeling technique, fully supported by the MBSE toolsets, engineers can see their options and conflicts (if any exist), and to pick their end desired product. Variation Points, Variants (options), and Dependencies can be defined, and relationships parametrized. Variable Elements can be linked to express required and excluded relationships. (ISO, 2013). Options can then be selected based on user goals, a configuration generated, and trade‐off analysis can take place on the resulting model.